Error monitoring in decision‐making and timing is disrupted in autism spectrum disorder. Issue 2 (28th November 2018) - Doenyas, Ceymi; Mutluer, Tuba; Genç, Egemen; Balcı, Fuat
Abstract : Individuals with autism spectrum disorder (ASD) have difficulties in social interactions. The cognitive domains that support these interactions include perceptual decision‐making, timing, and error‐monitoring, which enable one to appropriately understand and react to the other individual in communicative settings. This study constitutes a comprehensive exploration of decision‐making and interval timing in ASD as well as the first investigation of error‐monitoring abilities of individuals with ASD regarding their performance in the corresponding domains. We found that children with ASD fared similar to typically developing (TD) children in their first‐order task performance in two‐alternative forced choice perceptual decision‐making and temporal reproduction tasks as well as the secondary tasks (signal detection and free finger tapping tasks). Yet, they had a deficit in error‐monitoring in both tasks where their accuracy did not predict their confidence ratings, which was the case for the TD group. The difference between ASD and TD groups was limited to error‐monitoring performance. This study attests to a circumscribed impairment in error‐monitoring in individuals with ASD, which may partially underlie their social interaction problems. This difficulty in cognitively evaluating one's own performance may also relate to theory of mind deficits reported for individuals with ASD, where they struggle in understanding the mental states and intentions of others. This novel finding holds the potential to inform effective interventions for individuals with ASD that can target this error‐monitoring ability to have broad‐ranging effects in multiple domains involved in communication and social interaction. Autism Res 2019, 12: 239–248 © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Decision‐making, timing, and error‐monitoring are three of many abilities that underlie smooth social interactions. To date, these domains have been only investigated separately, but given their interactive role in social interactions that are impaired in ASD, we conducted the first study to investigate them together. Children with ASD were as successful as typically developing children in their task performances, but unlike them, were unaware of their errors in both decision‐making and timing tasks. This deficit that is limited to error‐monitoring can contribute to unraveling the unique cognitive signature of ASD and to formulating interventions with positive implications in multiple domains.